DNA barcoding of the tidal swamp rice (Oryza sativa) landraces from South Kalimantan, Indonesia - Dindin Hidayatul Mursyidin; Yudhi Ahmad Nazari; Badruzsaufari BADRUZSAUFARI; Muhammad Ridho Dinta Masmitra (Society for Indonesian Biodiversity, 2021)
Abstract. Mursyidin DH, Nazari YA, Badruzsaufari, Masmitra MRD. 2021. DNA barcoding of the tidal swamp rice (Oryza sativa) landraces from South Kalimantan, Indonesia. Biodiversitas 22: 1593-1599. The tidal swamp rice (Oryza sativa L.) landraces of the South Kalimantan, Indonesia, has been known for hundred years ago with a better adaptation to the local conditions, such as acidity, salinity, and metals contamination. However, the genetic insight of these landraces has not fully understood. Here, the rbcL region of tidal swamp rice from this region was successfully sequenced, aligned, analyzed, and deposited into the GenBank with accession numbers of MT818188–MT818201. The multiple alignments of these sequences showing a barcoding motif with eight mutation or polymorphic sites with both substitutions (transition-transversion) and indels (insertion-deletion). Based on this marker, the tidal swamp rice has a low genetic diversity, only 0.086. However, the UPGMA and maximum likelihood (ML) analyses revealed that this germplasm was grouped into five and twoclusters or clades, respectively. In this case, Bayar Putih is closely related to Siam Panangah and farthest from Lemo. This information might help to develop conservation and breeding programs of the tidal swamp rice landraces in the future.